2017
DOI: 10.1007/s40641-017-0069-7
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Numerical Modeling of Antarctic Ice-Sheet Dynamics

Abstract: Numerical modeling of the Antarctic ice sheet has gone through a paradigm shift over the last decade. While initially models focussed on long-time diffusive response to surface mass balance changes, processes occurring at the marine boundary of the ice sheet are progressively incorporated in newly developed state-of-the-art ice-sheet models. These models now exhibit fast, shortterm volume changes, in line with current observations of mass loss. Coupling with ocean models is currently on its way and applied to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 138 publications
0
55
0
Order By: Relevance
“…This requires the availability of surface velocity data covering the whole AIS, as well as spatially comprehensive data of ice shelf thinning over all major ice shelves. Recent advances in numerical modeling and improved coverage of surface velocity data across the AIS have, however, now made large-scale data assimilation of observed velocities possible (Cornford et al, 2015;Pattyn et al, 2017). Combined with robust estimation of ice shelf buttressing and its impact on ice flow (Arthern et al, 2015;Cornford et al, 2013;, direct measurements of ice shelf thickness change (Paolo et al, 2015) now allow us to quantify the instantaneous impact of observed ice shelf thinning on the ice sheet mass loss due to changes in buttressing, using wellestablished glacier-mechanical principles.…”
Section: 1029/2019gl085027mentioning
confidence: 99%
“…This requires the availability of surface velocity data covering the whole AIS, as well as spatially comprehensive data of ice shelf thinning over all major ice shelves. Recent advances in numerical modeling and improved coverage of surface velocity data across the AIS have, however, now made large-scale data assimilation of observed velocities possible (Cornford et al, 2015;Pattyn et al, 2017). Combined with robust estimation of ice shelf buttressing and its impact on ice flow (Arthern et al, 2015;Cornford et al, 2013;, direct measurements of ice shelf thickness change (Paolo et al, 2015) now allow us to quantify the instantaneous impact of observed ice shelf thinning on the ice sheet mass loss due to changes in buttressing, using wellestablished glacier-mechanical principles.…”
Section: 1029/2019gl085027mentioning
confidence: 99%
“…As a result, several key features of ice flow models have improved greatly, including: (1) the approximation used for the stress balance equations (Figure 3), (2) the discretization of model domains (Figure 4), and (3) the representation of grounding lines and ice front migration. This section summarizes these improvements; for more details on recent ISM development, we refer readers to Goelzer et al (2017) and Pattyn et al (2017).…”
Section: An Improved Generation Of Modelsmentioning
confidence: 99%
“…Glaciers and ice caps are too small to be resolved by their coarse spatial resolution. Ice sheets are large enough, but the main physical processes determining their response to climate change are still uncertain (Church et al, 2013;Deconto & Pollard, 2016;Pattyn et al, 2017). Also, their long time scale of adjustment and sensitivity to small circulation and temperature biases still make it challenging to include them in fully coupled models (Joughin et al, 2012;Lenaerts et al, 2015;Vizcaíno et al, 2010).…”
Section: Introductionmentioning
confidence: 99%